Equilibrium in Practice - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
In [1], it is proposed that n players are in equilibrium if all of their strategies yield highest possible expectation for the respective players. This equilibrium is related to the equilibrium proposed in this paper. In this paper, I propose an equilibrium where a group of n players are involved. Equilibrium of the group is equilibrium of the individual players since every player lives in group. Inspired from this conclusion, I propose that equilibrium of the individual players is the equilibrium of the group. To explain in plain and simpler words, equilibrium of the group is the equilibrium of the individual players since each player lives in the group.